Breve revisão de métodos de determinação de resíduos do herbicida á cido 2,4-diclorofenoxiacético (2,4-D) - De Amarante Jr., Ozelito Possidônio; Dos Santos, Teresa Cristina Rodrigues; Nunes, Gilvanda Silva; Ribeiro, Maria Lúcia [UNESP] (FapUNIFESP (SciELO), 2003)
This paper supplies a revision about the main techniques of extraction, clean-up and pre-concentration of the herbicide 2,4-dichlorophenoxyacetic acid (2,4-D) in water and soil samples, as well as chromatographic methods and immune assays for its identification and quantification.
Concise revision of methods for determination of the herbicide dichlorophenoxyacetic acid (2,4-D)
Keywords: 2,4-D; Chromatography; Immune assays; 2,4 dichlorophenoxyacetic acid; herbicide; chemical analysis; chromatography; concentration (parameters); extraction; immunoassay; quantitative analysis; review; soil analysis; water sampling